RETRACTED: The Pragmatic Function of Speech for Elementary Students: Indonesian Teaching in Australia - Setiawan Edi Wibowo; Aurora Adina Cholomeischi; Tudor Colomeischi; Kordula Schulze (Jurnal Prima Edukasia, 2023)
Following a rigorous examination and careful consideration of the article published in Jurnal Prima Edukasia entitled "The Pragmatic Function of Speech for Elementary Students: Indonesian Teaching in Australia" Vol 11, No 1, pp. 106-119, January 2023, DOI: http://dx.doi.org/10.21831/jpe.v11i1.54229 This article has been found to violate the publication principles of Jurnal Prima Edukasia and has been retracted. The article was proven to contain Gift Authorship. The document and its contents have been removed from Jurnal Prima Edukasia, and reasonable efforts should be made to remove all references/citations redirecting to this article. Permalink/DOI: http://dx.doi.org/10.21831/jpe.v11i1.54229